PERILAKU PENCARIAN INFORMASI ASN BADAN PENELITIAN DAN PENGEMBANGAN KABUPATEN LABUHANBATU - Sefri Doni; Siti Masliyah Lubis (Perpustakaan IPB, 2021)
Research and development plays an important role in improving government policies and administration. As a form of the government's seriousness in increasing the role of R&D in the administration of government, a concurrent division of affairs has been carried out starting from the central, provincial and district/city levels. The Labuhanbatu Regency Government through its Research and Development Agency has been handling R&D affairs since 2017. Even though it is only a few years old, the Labuhanbatu Regency research and development agency has succeeded in increasing the productivity of farmers' agricultural products in 2019 and was awarded the Very Innovative Regency category in the Innovative Government Award (IGA) in 2020. This success certainly cannot be separated from the support of the regional head and the civil servant in it. What is very interesting is related to the information used by civil servant in carrying out their duties. The information used is of course greatly influenced by the information seeking behavior it self. Research related to information seeking behavior has actually been done a lot but is dominant in the academic world. Using descriptive quantitative methods using the David Ellis model, the author tries to see the information seeking behavior of civil servant research and development agency Labuhanbatu Regency. The results of the study show that the civil servant research and development agency Labuhanbatu Regency has carried out a series of activities and structured steps in the search for information where the information that has been found is used as material in completing the work.